(untitled) (Global Journal of Human-Social Science, 2021)
La Libertad de ser libres (the freedom to be free) is an unpublished essay in which Hannah Arendt reflects on the relevance and the true meaning of the concept of freedom. The paper dates from 1967 in the United States, but it had not been published in its Spanish version until the summer of 2018 by Taurus publishing house (Barcelona, Spain). In this review, I attempt to reflect on the most important political ideas that the author presents in her essay on freedom and revolution, starting from comparing the American Revolution and the French Revolution. While the former was a great local success, the latter was a turning point in history but ended in disaster. Hannah Arendt’s essay reflects the strength and rigor of her political thought and the need to rethink the concept of revolution, with its possibilities and failures, and its implications for achieving freedom in public space, once in a free society a new beginning is possible, which connects with the most pressing challenges of our time.